Financial Supervisory Independence and Accountability-Exploring the Determinants - Masciandaro, Donato (IMF Working Papers; Working Paper, 2008)
We analyze recent trends in, and determinants of, financial supervisory governance. We first calculate levels of supervisory independence and accountability in 55 countries. The econometric analysis of the determinants indicates that the quality of public sector governance plays a decisive role in establishing accountability arrangements, more than independence arrangements. It also shows that decisions regarding levels of independence and accountability are not well-connected. The results also show that the likelihood of establishing adequate governance arrangements are higher when the supervisor is located outside the central bank.